(untitled) (GEON Journal (Management, Organizations and Business), 2017)
Speaking of research as something thoughtful, systematic, controlled and critical, it makes whoever gets involved in these tasks do it in a planned and organized way, for that reason the problem is defined, investigated and led to a response that allows to solve the problem, without However, we can develop all this with the words question to example: what (subject or question), for what (objective), why (problem), where (area), when (schedule), who (team) , with what (financing). When starting, it is the formulation of the problem that will mark the route, which will allow us to plan the investigation so that it leads us to an optimal result, for that reason it is important to formulate it in a statement that responds in a clear, precise and concrete way. And for what. In this planning, delimiting the subject and field of research helps to understand the scope both in possible results and the magnitude of the time necessary for its execution.